Local Thrombolysis for Successful Treatment of Acute Stroke in an Adolescent with Cardiac Myxoma. (2011) - Gassanov, Natig; Nia, Amir M.; Dahlem, Kristina M.; Ederer, Stefan; Wedemeyer, Inga; Caglayan, Evren; Erdmann, Erland; Er, Fikret
Abstract : Intracardiac myxomas are the most common benign cardiac tumors in adults. They are a rare source of cardiogenic embolisms and sudden death, especially in young patients. This report describes the case of a male adolescent who presented with right-sided paresis and aphasia. Magnetic resonance imaging of the brain revealed an ischemic stroke without evidence of acute bleeding. Intra-arterial local thrombolysis was immediately started. An echocardiographic screening after successful thrombolysis with a remarkable recovery of symptoms detected a thrombotic-like mass in the left atrium. The mass was excised surgically, confirmed as a benign atrial myxoma, and the patient was discharged with restitution ad integrum. Thus, contrary to some critical reports, thrombolytic therapy for acute ischemic strokes due to atrial myxomas may be safe and highly effective.